2021
DOI: 10.1038/s41398-021-01759-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between depression and metabolic syndrome and its components: a bidirectional two-sample Mendelian randomization study

Abstract: Observational studies suggested a bidirectional correlation between depression and metabolic syndrome (MetS) and its components. However, the causal associations between them remained unclear. We aimed to investigate whether genetically predicted depression is related to the risk of MetS and its components, and vice versa. We performed a bidirectional two-sample Mendelian randomization (MR) study using summary-level data from the most comprehensive genome-wide association studies (GWAS) of depression (n = 2,11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 71 publications
2
35
1
Order By: Relevance
“…A similar IVW analysis suggest the direction of influence is from MDD to MetS (40 genetic instruments, b = 0.23, SE = 0.06, p = 1.3E-04) rather than from MetS to MDD (108 genetic instruments, b = 0.015, SE = 0.011, p = 0.165). This comports with previous reports of the effect of depression phenotypes on metabolic dysregulation [ 17 , 23 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A similar IVW analysis suggest the direction of influence is from MDD to MetS (40 genetic instruments, b = 0.23, SE = 0.06, p = 1.3E-04) rather than from MetS to MDD (108 genetic instruments, b = 0.015, SE = 0.011, p = 0.165). This comports with previous reports of the effect of depression phenotypes on metabolic dysregulation [ 17 , 23 ].…”
Section: Resultssupporting
confidence: 90%
“…Some previous studies reported significant genetic correlation between MetS and depression phenotypes [ 17 , 23 ]. To compare estimates of genetic associations of MetS and PTSD with genetic associations of MetS and MDD, we computed genetic correlation estimates with MDD using the same summary statistics of metabolic traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs, NO 2 , and CO are related to biological toxicity (68-70). Similarly, higher levels of triglycerides and free fatty acids were observed among those living with depression, and it was reported that higher glucose concentrations of the pregenual anterior cingulate were associated with major depressive disorder (71)(72)(73). In a study from China, hyperlipidemia and hyperglycemia were related to cognitive impairment (53).…”
Section: Discussionmentioning
confidence: 92%
“…Research has found that patients with psychiatric disorders are known to have higher morbidity and mortality compared to the overall population [ 96 ]. This is likely due to the metabolic syndrome that these patients experience, predisposing them to cardiovascular diseases, type 2 diabetes, hypertension, dyslipidemia, hyperglycemia, and obesity [ 97 ]. Various aspects impact this high comorbidity, including genetic factors.…”
Section: Gene Variants Predicting Predisposition To Obesity and Metab...mentioning
confidence: 99%